(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Abstract- The study examined the behavior and conservation of the chinkara (Gazella bennetti), a species predominantly found in the semi-arid regions of western Rajasthan. Historically abundant across the Indian subcontinent, the chinkara now faces significant challenges due to habitat loss, poaching, and human-wildlife conflicts. The study explored the species’ behavioral ecology, including its unique mating rituals, territoriality, and maternal care. It also addresses the critical conservation issues impacting chinkara populations, highlighting the role of community-based conservation programs in mitigating these threats. Legal protections and habitat management strategies are evaluated, emphasizing the necessity of local community involvement in conservation efforts. Through an integrative approach combining ecological research and community engagement, this aimed to provide comprehensive insights into the effective conservation of the chinkara.